Accounting Principles Compliance – the True and Fair View Recipe. A Theoretical Perspective on the Contribution of Accounting Principles to the Financial Reporting Objective Achievement (I) - Claudia Cătălina CIOCAN (CECCAR Business Review, 2021)

(untitled)
This paper explores the significance of the true and fair view, as the main objective of financial reporting to which accounting principles are subordinated, and the relationship between it and all accounting principles, focusing on identifying their contribution to achieving the true and fair view and, simultaneously, the potential conflicts. To address this issue, several interpretations of the true and fair view objective were analyzed together with the way the requirements of each accounting principle contribute to the achievement of this objective. The paper highlights that the true and fair view recipe involves contributions such as aggregating values from different reporting periods, separately reflecting assets and liabilities to prevent hiding part of a company’s wealth or masking the risks that the company is facing, accurate, neutral and free from error/omission representation of transactions, establishing an acceptable materiality level that does not allow information to be over contracted or overcrowded with insignificant details, reflecting the economic substance of the transaction instead of the legal one, a realistic and balanced estimation of the risks and value losses, the presentation of past rights and obligations without being limited by their effective settlement date.